Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The role of Flexibility-Building Techniques in The development of Administrative processes and Performance Management from The perspective of the administrative staff at Tabuk University Dr. Najwa Mufawez Mofeez Al-Fawaz 2. The Role of Human Resource Management in Enhancing Positive Psychological Capital among Employees in Government Sector in Saudi Arabia in light of Vision 2030, in Riyadh Sarah Hamoud Al-Hamali Al-Qahtani , Sarah Mubarak Al-Dosari, Amal Abbas Al-Tawili 3. The impact of Lean management on achieving Functional Creativity, an applied study at Taif University Dr. Samia Ayed Al-Jaeed, Remas Ahmad Al-Thbaity 4. A Proposal to Activate the Collective Waqf Platform Using the Blockchain Platform - Jordan as an Example - Qusai Mahmoud Sindyani, Bayan Zuhier Ababneh 5. Banking Merger, Challenges & Its Impact on the Financial Performance of Sudanese Banks: Empirical Study- Blue Nile Mashreq Bank (2015-2020) Dr. Omer Ali Babiker El-Tahir